Answer: 207
Step-by-step explanation:
Answer:
the answer is c
Step-by-step explanation:
Answer:
0
Step-by-step explanation:
The possible solution to the equation given is 3 and -1/3
<h3>Laws of logarithm</h3>
Given the logarithmic expression given as:
log,(8x) – log,(x^2 - 1) = log, 3
Applying the product and quotient rule will give:
log(8x/x^2-1) = log3
8x/x^2-1 = 3
Cross multiply
8x = 3x^2 - 3
3x^2 - 8x - 3 = 0
3x^2 -9x + x - 3 = 0
3x(x-3)+1(x-3)
x - 3 = 0 and 3x = -1
x = 3 and -1/3
Hence the possible solution to the equation given is 3 and -1/3
Learn more on logarithm here: brainly.com/question/25710806